2013
DOI: 10.2340/00015555-1465
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization to Skin-associated Microorganisms in Adult Patients with Atopic Dermatitis is of Importance for Disease Severity

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease. Environmental and genetic factors, as well as microbial products from yeasts and bacteria, play a role in triggering the disease. A cohort of 619 adult patients with AD was screened for severity of AD, sensitization to Malassezia sympodialis, Candida albicans, Staphylococcus aureus enterotoxins and Dermatophagoides pteronyssinus. Serum levels of interleukin (IL)-18 were measured. Immunoglobulin E (IgE) sensitization to the combination of both yeast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 52 publications
3
44
0
2
Order By: Relevance
“…Another study on 619 adult patients from Sweden showed a correlation between the severity of AD and the combined IgE sensitisation to dust mites and yeasts such as Malassezia spp. and C. albicans (19).…”
Section: Discussionmentioning
confidence: 99%
“…Another study on 619 adult patients from Sweden showed a correlation between the severity of AD and the combined IgE sensitisation to dust mites and yeasts such as Malassezia spp. and C. albicans (19).…”
Section: Discussionmentioning
confidence: 99%
“…AD is also more highly associated with sensitization to C. albicans , compared with other fungal species [26]. Increased Candida -specific IgE also correlates with severity of disease [32]. These findings suggest that C. albicans could be an unforeseen contributor to AD pathogenesis and supports a need for further fungal microbiota analysis on a larger scale.…”
Section: Fungal Microbiome Of the Skinmentioning
confidence: 99%
“…A key priority for allergy research will be to determine whether these apparent associations are confirmed by further unbiased, high-throughput sequencing methods; and if so, the extent to which the bacterial flora of mite pests may modulate conditions such as atopic dermatitis (Sonesson et al 2013). A key priority for allergy research will be to determine whether these apparent associations are confirmed by further unbiased, high-throughput sequencing methods; and if so, the extent to which the bacterial flora of mite pests may modulate conditions such as atopic dermatitis (Sonesson et al 2013).…”
Section: Outcomes and Perspectivesmentioning
confidence: 99%